2020
DOI: 10.9734/ijecc/2020/v10i930246
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drought Characteristics Using the Reconnaissance Drought Index (RDI) over Parambikulam Aliyar Basin of Tamil Nadu

Abstract: Drought tends to be a creeping phenomenon occurs gradually with the deficiency in rainfall further extending its impact on sectors which are dependent on water. The drought characteristics were analysed in Parambikulam Aliyar Project (PAP) basin based on the European Centre for Medium range Weather Forecasts Interim Reanalysis (ERA-Interim) gridded data with resolution of 0.125° ×0.125° during 1981-2017. Reconnaissance Drought Index (RDI) was applied for monitoring the drought. The variables used in RDI are ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Several researchers around the globe have effectively utilized the rainfall deficit index to gain a deeper understanding of drought dynamics. For example, Topçu and Seçkin (2021) conducted a study in Turkey and identified a mild drought, while Guhan et al (2020) in Tamil Nadu detected severe and mild drought events. Similarly, Asadi and Vahdat (2013) highlighted the efficacy of RDI in monitoring drought in Iran.…”
Section: Rainfall Deficit Indexmentioning
confidence: 99%
“…Several researchers around the globe have effectively utilized the rainfall deficit index to gain a deeper understanding of drought dynamics. For example, Topçu and Seçkin (2021) conducted a study in Turkey and identified a mild drought, while Guhan et al (2020) in Tamil Nadu detected severe and mild drought events. Similarly, Asadi and Vahdat (2013) highlighted the efficacy of RDI in monitoring drought in Iran.…”
Section: Rainfall Deficit Indexmentioning
confidence: 99%